Study of Effect of Chest Physical Therapy in Patients with Chronic Obstructive & Acute Suppurative Lung Diseases (Journal of Fatima Jinnah Medical University, 2018)
Background: In airway diseases, decline in pulmonary functions, mucus hypersecretion and airway clearance always remain a big problem. Manual chest physiotherapy techniques involving chest percussion, vibration and shaking have long been used in the treatment of respiratory conditions. There is limited study of CPT effectiveness in these diseases. We applied different CPT techniques in different respiratory conditions to understand its effectiveness. Objective: The goal of this study is to know the effectiveness of different chest physical therapy techniques in patients with chronic obstructive , acute suppurative lung diseases and also to educate these patients about the benefits of bronchial hygiene therapy, breathing exercises and other protocols of chest physical therapy along with conventional treatment Settings: This study was done in chest physiotherapy department of Gulab devi chest hospital from june 2012-dec 2012. . Method: This study includes 51 subjects(n=51) with mean age 45 years, out of which 18 patients were with COPD and 15 with br.asthma and they were diagnosed on the basis of clinical & spirometric findings PEFR, FEV1, FVC &FEV1/FVC ratio. Bronchiectasis, pneumonia and lung abscess diagnosed in 11, 4 and 3 patient respectively on the basis of clinical judgementct, CXRs PA & CT scan chest. CPT techniques like aerosol therapy,bronchial hygiene therapy( BHT), postural drainage purcussion vibration(PDPV), active cycle breathing(ACB), and different cuff & huff techniques were applied for 1week and observe the effect after 7days. Results: In COPD patients ,SaO2 improved from 89% to 98% in about 88% patients, sputum clearance in 70% and dyspnea improved in 67% of patient but there was no marked improvement in FEV1 & PEFR.In 65% of asthma patients SaO2 improved from 90 to 97% and PEFR in 80% of patient. While in bronchiectasis ,pneumonia and lung abscess sputum load decrease in 80%, 75% and 66% of patient respectively.WBCs count normalized in 75% of patient, (12500/ul to 10500/ul). Conclusion: There is a positive effect of chest physiotheray (CPT) in all respiratory diseases which ae associated with hypersecretion or retention of sputum and dysponea. It makes prognosis better
Keywords: Respiratory care of lung diseases; suppurative lung diseases; Chest physiotherapy; lung abscess; Postural drainage; COPD; pneumonia.